Tin (II) Chloride Catalyzed Esterification of High FFA Jatropha Oil: Experimental and Kinetics Study - Kusumaningtyas, Ratna Dewi; Handayani, Prima Astuti; Rochmadi, Rochmadi; Purwono, Suryo; Budiman, Arief (International Journal of Renewable Energy Development, 2014)
Biodiesel is one of the promising energy source alternatives to fossil fuel. To produce biodiesel in a more economical way, the employment of the low-cost feed stocks, such as non-edible oils with high free fatty acid (FFA), is necessary. Accordingly, the esterification reaction of FFA in vegetable oils plays an important role in the biodiesel production. In this work, esterification of FFA contained in Crude Jatropha Oil (CJO) in the presence of tin (II) chloride catalyst in a batch reactor has been carried out. The esterification reaction was conducted using methanol at the temperature of 40-60 Â°C for 4 hours. The effect of molar ratio of methanol to oil was studied in the range 15:1 to 120:1. The influence of catalyst loading was investigated in the range of 2.5 to 15% w/w oil. The optimum reaction conversion was obtained at 60 Â°C with the catalyst loading of 10% w/w oil and molar ratio of methanol to oil of 120:1. A pseudo-homogeneous reversible second order kinetic model for describing the esterification of FFA contained in CJO with methanol over tin (II) chloride catalyst was developed based on the experimental data. The kinetic model can fit the data very well.